Implementation of the Climate-Smart village approach - Nägeli Juan, Laia; Murray, Una; McKeown, Peter C.; Styles, David; Spillane, Charles; Bonilla Findji, Osana; Martínez Barón, Deissy (2018)
Climate change is affecting global population and agriculture. Through climate-smart agriculture practices in climate-smart villages, it promotes adaptation, builds resilience to climatic stresses and ensures food security. This research thesis aims to support the planning and decision-making processes to promote and scale out climate-smart agriculture among smallholder farmers in Colombia. The research thesis analyzed the data from a Gender-sensitive Smart Household Monitoring instrument to assess climate-smart agriculture performance and outcomes in Cauca climate-smart village. Data was analyzed through different indicators tracked at household level disaggregated by gender and examines the Climate-smart agriculture adoption and dis-adoption trends and related factors (financial, technical/operational and social) that enable its implementation. The study found that climate-smart practices related to water and ensure food security during the year are the most preferred. This study highlights the importance of climate informatics services to promote a higher adaptation to climate change. Furthermore, this study give a recommendation to improve the surveys to future monitoring instruments to address correctly smallholder farmers and practitioners to scale out climate-smart agriculture.